Gambaran Kesehatan Jiwa Relawan Remaja dalam Penanggulangan Bencana - Hidayah, Nurul; Florensa, Florensa; Seprian, Dwin; Fathudin, Yogasliana (Universitas Malahayati, 2023)
ABSTRACT Mental health is a good emotional and psychological state, in which individuals can utilize their cognitive and emotional abilities, function in their communities, and meet their daily needs. The essence of mental health itself is more about the existence and maintenance of a healthy mentality. Disaster conditions will have various physical and psychological impacts for each individual, including disaster volunteers. This study aims to determine the description of mental health which includes emotional mental disorders, namely depression, anxiety and PTSD in adolescent volunteers in carrying out disaster management. This type of research is a descriptive research type, taking this sample using a total sampling technique. The research respondents were youth volunteers who were involved in flood disaster management in Melawi Regency who were members of the TSR-PMI and youth volunteers who were members of the West Java HIPGABI volunteer team who were directly involved in the Cianjur earthquake disaster management. The sample instrument is in the form of a digital questionnaire (Google Form) which is distributed through the Whatsapp Group communication network. The questionnaire used was a translated SelfReporting Questionnaire 29 questionnaire. The proportion of poor mental health was greater in the female sex (57%) compared to the male sex (44%). Furthermore, the proportion of poor mental health is greater in those aged 17-19 years (57%) compared to those aged 20-21 years (44%).The symptoms experienced by youth volunteers when they were involved in disaster management were the emergence of 3 complaints with the highest percentage not sleeping well (46%), getting tired easily (43%) and finding it difficult to make decisions (38%). Keywords: Mental Health, Adolescents, Disaster ABSTRAK Kesehatan jiwa merupakan suatu keadaan emosional dan psikologis yang baik, dimana individu dapat memanfaatkan kemampuan kognisi dan emosi, berfungsi dalam komunitasnya, dan memenuhi kebutuhan hidupnya sehari-hari. Inti dari kesehatan mental sendiri adalah lebih pada keberadaan dan pemeliharaan mental yang sehat. Kondisi bencana akan memberikan berbagai dampak fisik maupun psikologis bagi setiap individu tidak terkecuali pada relawan bencana. Penelitian ini bertujuan untuk mengetahui gambaran kesehatan jiwa yang meliputi gangguan mental emosional yakni depresi, kecemasan dan PTSD pada relawan remaja dalam melakukan penanggulangan bencana. Jenis penelitian ini ialah jenis penelitian deskriptif, pengambilan sampel ini menggunakan teknik total sampling. Responden penelitian ialah relawan remaja yang terlibat dalam penanggulangan bencana banjir di Kabupaten Melawi yang tergabung dalam TSR-PMI dan relawan remaja yang tergabung dalam Tim relawan HIPGABI Jawa Barat yang terlibat langsung dalam penanggulangan bencana gempa Cianjur. .Instrumen sampel berupa kuesioner digital (Google Form) yang disebar melalui jejaring komunikasi Whatsapp Group. Kuesioner yang digunakan merupakan kuesioner SelfReporting Questionneire 29 yang sudah diterjemahkan. Proporsi kesehatan mental yang buruk lebih besar terdapat pada jenis kelamin perempuan (57%) dibandingkan dengan jenis kelamin laki-laki (44%). Selanjutnya proporsi kesehatan mental yang buruk lebih besar terdapat pada usia 17-19 Th (57%) dibandingkan dengan usia 20- 21 Th (44%).Gejala yang dialami relawan remaja saat terlibat dalam penanggulangan bencana yakni munculnya 3 keluhan dengan persentase tertinggi adalah tidak tidur dengan nyenyak (46%), mudah lelah (43%) dan merasa sulit untuk membuat keputusan (38%). Kata Kunci: Kesehatan Mental,Remaja, Bencana